Pathomorphological features of the uterus’ wall structure in case of fetuses with a gestational term of 37-40 weeks from mothers with a chronic infection of the lower genital tracts - Kupriianova, L.; Ivanchenko, S. (Journal of Education, Health and Sport, 2021)
In the following article we have provided a data towards a comprehensive research of the pathomorphological features of the uterus’ wall structure in case of fetuses from mothers with HILGT comparing to ones in case of fetuses from healthy mothers. The research methods: macroscopic, organometric, histological, immunohistochemical, morphometric, statistical. On the basis of the organometric research we have revealed a probable decrease of the weight, length and thickness indexes likewise one of the main components of the uterus wall in case of fetuses from mothers with a complicated pregnancy comparing to ones in case of fetuses from healthy mothers. By applying histological method we have revealed an increased growth of the connective tissue both in the endometrium and myometrium in case of fetuses from mothers with HILGT relatively to one in case of fetuses from mothers with a physiological pregnancy. Moreover, the massive growth of the collagen fibers leads to the disorder in the strucutral organization of the muscle component. The uterus’ endometrium in case of fetuses from the main group could be characterized by a few glands without features of the functional activity comparing to one in case of fetuses from the group of comparison. In the structure of the connective tissue in case of uterus of fetuses from mothers with a complicated pregnancy we have revealed mainly the collagen of the III type, while the collagen of the I type could be revealed in the form of small loci of reduced intensity of glow. By applying the immunohistochemical method we have revealed an increase of the apoptotic index in the endometrium of fetuses from mothers with a chronic infection of the lower genital tracts comparing to one in case of fetuses from healthy mothers. By applying MCAT to endotheline-1 we have revealed an increased glow of the endtheliocytes in the vessels both of arterial and venous types, in case of fetuses from the main group comparing to one in case of fetuses from the group of comparison. In the uterus of fetuses from mothers with HILGT we could observe a decreased hormon producing activity comparing to one in case of fetuses from mothers with a physiological pregnancy. All changes, that were revealed in the uterus of fetuses from mothers with an infectious pathlogy declare an existance of the severe disorder in the implementation and formation of main organ’s components, as well as are caused mainly by a chronic hypoxia as well as influence of the infectious agent. All pathomorphological features of the uterus wall structure in case of fetuses from mothers with HILGT, that were revealed, could contribute subsequently to the complications in the pregnancy’s onset as well as could lead to the disruption of one.